Framework for Evaluating the Effectiveness of Telecommunications Regulators in Sub-Saharan Africa - Attenborough, Nigel (World Bank, Washington, DC, 2014)
This report develops an assessment framework and decision-making tool that, it is hoped, will facilitate evaluations of the effectiveness of telecommunications regulators in sub-Saharan Africa by the regulators themselves, World Bank staff, other institutions and their consultants. The assessment framework has been developed as part of a larger study in which the framework was developed and then applied in three sub-Saharan African countries, Mauritania, Uganda and South Africa. The individual country assessments are attached to this report as appendices. In the context of this framework, the adoption of a broad and dynamic definition of effectiveness or regulatory efficiency encompasses both the legal and regulatory framework design and the extent to which it has affected the regulator's influence on the sector, as well as the implementation of the framework, regulatory practice, the regulatory decisions taken and their outcomes. The structure of the report is as follows. Section 2 sets out the rationale for using the analytical framework. Section 3 explains the framework's logic and the assessment's role in it. A step-by-step instruction guide to conducting assessments can be found in Section 4. Background material for conducting assessments is laid out in the following three sections: section 5 contains the normative reference point of the assessment; section 6 covers the background data required together with the detailed questionnaire to be used by the evaluator; section 7, provides a menu of options for corrective action which can be used, following assessments, to choose possible solutions to the impediments identified. Finally, Section 8 offers an illustration of how the framework might be used, by examining the issue of licensing in the three sub-Saharan African countries assessed.